Identification of Critical Variables in Cost Estimating for Building Conservation Works. - Lim , Yoke Mui
As conservation works gain popularity in recent years, the issue of inaccurate estimation of conservation cost has become more apparent. Although estimators are able to accurately estimate the cost of a new building, the same cannot be said for building conservation works. Conservation works are complex,non-standard and the scope of works depends on the conditions of each Individual building.